Academic Resilience of Adolescent Students During COVID-19 Pandemic Situation - Borah, Munmi; Sultana, Yeasmin (JOURNAL OF INDIAN EDUCATION, 2022)
Present paper tries to find out the academic resilience of adolescent students in the COVID-19 pandemic situation with reference to their socio-economic status and location. Descriptive survey research method has been followed in this study. The sample of the study comprises 150 adolescent students belonging to Grade IX from Provincialised high schools of Jorhat district, Assam. Data were collected personally by the investigators with the help of an academic resilience Scale. Simple percentage, t‑ test, ANOVA and Post-hoc test was used for analysing the data. 42.67 per cent of the adolescent students were found to have Moderate academic resilience level and 32.67 per cent and 4 per cent of the adolescent students were found to have low and extremely low academic resilience level. Remaining 20 per cent of the adolescent students were found to have high academic resilience level. Significant difference was found in the adolescent students’ academic resilience level in the COVID-19 pandemic situation when compared with reference to their location and socio-economic status.